Host–symbiont plasticity in the upside-down jellyfish Cassiopea xamachana: strobilation across symbiont genera - Sharp, Victoria; Kerwin, Allison H.; Mammone, Marta; Avila-Magana, Viridiana; Turnham, Kira; Ohdera, Aki; LaJeunesse, Todd; Medina, Mónica (Frontiers in Ecology and Evolution, 2024)
In the upside-down jellyfish, Cassiopea xamachana (Cnidaria: Scyphozoa), the establishment of photosymbiosis with dinoflagellates (family Symbiodiniaceae) is necessary for the sessile polyp to undergo metamorphosis (strobilation) into a free-swimming adult. C. xamachana has the capacity to associate with a wide variety of dinoflagellate species and representatives of different genera. While some studies have looked at the successful induction of symbiosis, none to date have examined the lasting effect of diverse symbiont taxa on host survivorship and development, which is needed to assess the viability of such symbioses. Our study exposes C. xamachana polyps to 22 different cultured Symbiodiniaceae strains representing 13 species from 5 genera; and analyzes the time to strobilation, the number of ephyra (juvenile medusa) produced, and the proportion of ephyra that died prematurely. Here we show that C. xamachana strobilation can be induced by most symbiodiniacean strains we tested, with the exception of free-living species (i.e., unknown to establish symbiosis with any other marine host). Additionally, ephyrae did not display morphological variation or survivorship differences with varying symbionts. However, we observed intraspecific variation in time to induce strobilation with different strains. This work expands the known symbiont species that can form stable mutualisms with C. xamachana, primarily in the genera Symbiodinium and Breviolum. Additionally, we provide evidence of differences in the ability of cultured symbiodiniaceans to establish symbiosis with a host, which suggests population-level differences in dinoflagellate cultures impact their symbiosis success. By utilizing ananimal like C. xamachana with flexible symbiont uptake, we are able to explore how symbiont diversity can influence the timing and success of symbiosis-driven development. Introduction 2 Author Contributions Protocols were developed by AK, VAM, and AO for C. xamachana husbandry and symbiont infection. The first experiment was developed by AK and executed by VS. Second and third experiments were designed and executed by VS and MoM. Symbiodiniaceae cultures provided by TL and KT. 28S sequencing protocol provided and taught by KT. Symbiodiniaceae DNA extraction and sequencing performed by MaM and VS. Manuscript written by VS and edited by all authors.